Minimally Invasive Glucose Monitoring Using a Highly Porous Gold Microneedles-Based Biosensor: Characterization and Application in Artificial Interstitial Fluid - Tasca-Gottardo, F; Tasca-Gottardo, F (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
In this paper, we present the first highly porous gold (h-PG) microneedles-based second-generation biosensor for minimally invasive monitoring of glucose in artificial interstitial fluid (ISF). A highly porous microneedles-based electrode was prepared by a simple electrochemical self-templating method that involves two steps, gold electrodeposition and hydrogen bubbling at the electrode, which were realized by applying a potential of −2 V versus a saturated calomel electrode (SCE). The highly porous gold surface of the microneedles was modified by immobilization of 6-(ferrocenyl)hexanethiol (FcSH) as a redox mediator and subsequently by immobilization of a flavin adenine dinucleotide glucose dehydrogenase (FAD-GDH) enzyme using a drop-casting method. The microneedles-based FcSH/FAD-GDH biosensor allows for the detection of glucose in artificial interstitial fluid with an extended linear range (0.1–10 mM), high sensitivity (50.86 µA cm−2 mM−1), stability (20% signal loss after 30 days), selectivity (only ascorbic acid showed a response about 10% of glucose signal), and a short response time (3 s). These properties were favourably compared to other microneedles-based glucose biosensors reported in the literature. Finally, the microneedle-arrays-based second-generation biosensor for glucose detection was tested in artificial interstitial fluid opportunely spiked with different concentrations of glucose (simulating healthy physiological conditions while fasting and after lunch) and by placing the electrode into a simulated chitosan/agarose hydrogel skin model embedded in the artificial ISF (continuous glucose monitoring). The obtained current signals had a lag-time of about 2 min compared to the experiments in solution, but they fit perfectly into the linearity range of the biosensor (0.1–10 mM). These promising results show that the proposed h-PG microneedles-based sensor could be used as a wearable, disposable, user-friendly, and automated diagnostic tool for diabetes patients. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.